Status of the mother tongues in the 2021 census of Nepal - Regmi, Dan Raj (Journal of Nepalese Studies, 2024)
Mother tongues belonging to different genealogy present an appalling view in terms of vitality and levels of language use. The 2021 census has identified 124 mother tongues belonging broadly to four major language families, viz., Indo-European, Sino-Tibetan, Austro-Asiatic and Dravidian including one language isolate. There are 47 Indo-European mother tongues. They are spoken by 83.07% of the total population. The numbers of Sino- Tibetan and Austro-Asiatic mother tongues amount to 72 and three, respectively. They are spoken by 16.59% and 0.19% of the total population, respectively. Dravidian and language isolate each counts single language spoken by less than one percent. The mother tongues broadly belonging to major language families further belong to different sub-groups. Only16.9% of the total mother tongues are destined to have speakers more than 1,00,000. Of such mother tongues, 13 belong to Indo-European and 8 belong to Sino-Tibetan. Only 47.6% mother tongues are safe. Around 30.6% are vulnerable and8.9% are shifting. Around 52.4% mother tongues are facing different labels of endangerment. Around 43.46% mother tongues have sustainable levels of language use. The existing anomalies appeared in the counting of the mother tongues may be mitigated by conducting a separate language census and framing a formal language policy.